Reflections on trauma, symbolization and psychic pain in a case of neurosis and a case of psychosis1. (5th April 2016) - Maldonado, Jorge Luis; Solimano, Alberto Luis
Translations of summary: This paper seeks to advance some considerations on trauma, historical reality, its symbolization and the psychic pain generated by the investigation of unconscious processes in psychoanalytic treatment. These themes will be explored by demonstrating the differences arising between traumatic experiences and their expression in phantasy, as they occurred in a case of neurosis and another of psychosis. In each case, the differences in the features of the symbolization and the processes of working through shall also be taken into consideration. Particular attention shall be paid to the specific difficulties encountered by the analyst in the interpretative treatment of the trauma resulting from the amount of psychic pain induced in the patient, which at times proves to be an insurmountable barrier and a destructive distortion of the process.